Análise de cenários para auxílio à tomada de decisão no plantio mecanizado de cana-de-açúcar - Nardo, Luiz Augusto de Souza [UNESP] (2015)
With the mechanization advance in the sugarcane farming cycle, they have been instrumental studies for improvement in processes from the soil preparation to harvester. The analysis of best planting scenarios for later harvest coupled with the autopilot use requires knowledge of the areas of systematization and labor- skilled workers to ensure the quality of the process and reduce damages focusing on the variables described below. Therefore, the objective is to evaluate planting scenarios coupled with the use of software and autopilot in the culture of sugarcane, using as travel time assessment and maneuver, distance traveled, number of maneuvers, fuel consumption among others, focusing the maximum optimization of these factors. The study was conducted in the municipality of Tanabi, SP, during planting, 2013. The study showed a decrease of up to 25 % in the number of maneuvers increasing machine availability and reducing costs